Performance Analysis of the Robusta Coffee Supply Chain in the Agroindustry Using the SCOR Model (a Case Study at PT. Harta Mulia Blitar) - Ardiella Sukma Maheswari; Sri Tjondro Winarno; Dona Wahyuning Laily (Journal of Global Sustainable Agriculture, 2026)
PT. Harta Mulia, Blitar is a robusta coffee producer. The company faces challenges in meeting production targets due to various factors, such as sales fluctuations and raw material procurement that does not align with production plans. This study aims to analyze supply chain performance and propose strategies to improve the management of the robusta coffee supply chain at PT. Harta Mulia, Blitar. The methods used in this study include the Supply Chain Operation Reference (SCOR) analysis and the Analytical Hierarchy Process (AHP). SCOR and AHP analysis were employed to measure and evaluate the performance of the robusta coffee supply chain at PT. Harta Mulia, Blitar. The study found that the supply chain performance scored 88,72 which falls into the average category. A strategy companies can implement to elevate their supply chain performance to the "excellent" category is to focus on several Key Performance Indicators (KPIs), namely production planning, material planning, supplier on-time delivery performance, and product replacement time. This is because these indicators currently fall below the overall supply chain performance benchmark, making it crucial to prioritize them through the use of demand-driven methods and production planning adjustments to improve production planning, digitizing raw material tracking and establishing agreements with suppliers for material planning, seeking alternative suppliers that meet company standards to avoid reliance on a single supplier to address supplier on-time delivery performance, and tightening quality control (QC) while maintaining ready-to-ship inventory as a solution to product replacement time challenges